Adherence to Healthy Lifestyle among Hypertensive Patients and Its Association with Anthropometric Measures - Zahra Sedaghat; Mohammad Javad Zibaeinejad; Mohammad Fararouei (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: The risk of coronary heart diseases is highly associated with our lifestyle. To reduce or prevent diseases including coronary, diabetes and many types of cancers we need to adhere to proper lifestyle which seems not to be easily achievable. The aim of this study was to measure adherence to healthy lifestyle among hypertensive patients and its association with anthropometric measures. Methods: Patients with high blood pressure, but no history of cardiovascular diseases (n=140) were participating in this correlation study. An interviewer administered questionnaire was used to collect required information. Data was analyzed using STATA12. Descriptive statistics (medium & SD) for qualitative variables and frequency, per cent for qualitative variables were used. Results: Despite the fact that more than 86% of the participants reported adhering to suggested healthy habits, data on their current lifestyle suggested less than 12% of the participants were adhering at least one significant healthy change in their diet or physical activity. However, among those who were smokers before being aware of their problem, 60% successfully stopped smoking. Higher BMI was related to non-adherence to healthy lifestyle (p<0.05). Conclusion: Even after being informed of the higher risk of coronary diseases, patients with hypertension were not able to fully adhere to healthy habits and quit smoking. Paper Type: Research Article.